A Proposal Framework for a Tri-National Agreement on Biological Conservation in the Gulf of Mexico Large Marine Ecosystem. (May 2022) - Strongin, Kyle; Lancaster, Alana Malinde S.N.; Polidoro, Beth; Aguilar-Perera, Alfonso; Gerber, Leah; Díaz, Patricia González; González-Méndez, Juliett; McKinney, Larry; Pérez, Héctor Espinosa; Pech, Daniel; Rojas, Dorka Cobián; Saul, Steven; et al.
Abstract: International agreements have been used to focus global attention on areas of both marine and terrestrial conservation concern. Currently, The Convention for the Protection and Development of the Marine Environment in the Wider Caribbean Region, known as the Cartagena Convention (Cartagena), is the only multilateral environmental agreement in force tht governs the marine environment of the Gulf of Mexico Large Marine Ecosystem (GoM-LME). The GoM-LME provides diverse habitats to maintain the high diversity of species, including endemic and endangered species, and provides natural resources for the United States, Cuba, and Mexico. This paper investigates the legal frameworks, currently recognized in the GoM-LME, to build a proposed tri-national framework. We investigated the selected multilateral agreements which currently govern conservation practices in the GoM-LME, and provide the legal context for decision-making at the national level. In addition, gaps in areas such as pollution, oil spill response, and species conservation were identified, providing the basis for the development of us to propose key elements of a tri-national agreement for the governance and biological conservation in the GoM-LME. The creation of a tri-national agreement which focuses conservation efforts in the Gulf of Mexico between the three GOM-LME countries, would allow their specific, regional conservation concerns to be comprehensively addressed.